Caesarean section among immigrants with different obstetrical risks. Issue 3 (8th March 2018) - Trinh, Lieu Thi Thuy; Assareh, Hassan; Achat, Helen; Chua, Seng; Guevarra, Veth
Abstract: Aim: To determine the variation in caesarean section rates among immigrant populations. Background: Australia is one of the most multicultural in the world and is also among those with the highest caesarean section rates. Design: Secondary data analysis. Methods: Routinely collected data from a Local Heath District between 2011 and 2015 were analysed. Women were categorized into regional groups based on country of birth. Obstetrical risk was classified using the Robson classification. Results/Findings: In total 48 711 women gave birth, of whom 64.0% were born overseas; 13 966 had a caesarean section (28.7%). South and Central Asia women had a high number of caesarean sections ( n = 4139; 29.6% of all caesarean sections), a high overall adjusted caesarean section rate (31.4%; 95% CI, 30.5%–32.3%), and consistently high caesarean section rates among women with single cephalic term pregnancy without a previous caesarean section. High adjusted caesarean section rates were seen among South East Asia women with nulliparous, single cephalic, term pregnancy, and spontaneous labour. Demographic and clinical characteristics explained 83.5% of the variation in overall caesarean section rates between country of birth and 21.8% to 100% depending on Robson group. Conclusions: Caesarean section rates varied by country of birth and within some Robson groups. The studied factors had various effects on the variation in caesarean section rates between country of birth and Robson groups. SUMMARY STATEMENT: What is already known about this topic? Australia has a high caesarean section rate The caesarean section rate varies by country of birth and by Robson group. The extent of the variation in caesarean section rate between country of birth within each Robson group is unknown. What this paper adds? The caesarean section rate varies by country of birth for all Robson groups combined and for Robson groups 1 to 4. Women from South and Central Asia and South East Asia have a higher rate of caesarean section. The studied factors explained most of the variation in overall caesarean section rates between country of birth (83.5%) and 21.8% to 100% depending on Robson group. The implications of this paper: Future studies should explore the reasons behind the higher rates among some groups of women. Information including partners, extended family, time living in Australia, immigrant status, and feto‐pelvic disproportion should be included whenever possible. Efforts to reduce the caesarean section rate such as health education through antenatal classes should focus on groups of women with high rate of caesarean section. Subsidized antenatal classes in suitable community languages might be useful. Health professionals should be aware of groups of women with higher risk of caesarean section.